2000
DOI: 10.1007/s004240000372
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ and electrolyte mobilization following agonist application to the pancreatic β cell line HIT

Abstract: We have investigated intracellular Ca2+ mobilization in oscillations of cytoplasmic Ca2+ in response to glucagon-like peptide 1 (GLP-1) and glucose in clonal HIT insulinoma cells with a confocal laser-scanning microscope (CLSM). We also used electron probe X-ray microanalysis to determine the GLP-1- and glucose-induced changes in electrolyte levels in the cytoplasm and insulin granules of the cells. GLP-1 produced 10- to 35-s duration oscillations in cytoplasmic Ca2+ concentration ([Ca2+]i), both with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…3C) (62). Our studies suggest that GLP-1 application results in oscillations in [Ca 2ϩ ] i in HIT-T15 cells and that these oscillations are not abolished (although they are diminished in amplitude) by removal of extracellular Ca 2ϩ or by VDCC blockade (Fig.…”
Section: Glp-1 and Insulin Secretionmentioning
confidence: 74%
“…3C) (62). Our studies suggest that GLP-1 application results in oscillations in [Ca 2ϩ ] i in HIT-T15 cells and that these oscillations are not abolished (although they are diminished in amplitude) by removal of extracellular Ca 2ϩ or by VDCC blockade (Fig.…”
Section: Glp-1 and Insulin Secretionmentioning
confidence: 74%
“…Interplay between calcium and cAMP in human sperm appears to be different because cAMP achieves exocytosis in the presence of high concentrations of EGTA, which chelates extracellular calcium, preventing an influx from the outside, but not of low concentrations of 1,2-bis(2-aminophenoxy)ethane-N,N,NЈ,NЈ-tetraacetic acid-acetoxymethyl ester, which chelates intracellular calcium, preventing mobilization from stores (8). Interestingly, cAMP-elevating agents such as GLP-1 stimulate the release of calcium stored in insulin-containing secretory granules (85). In this study we show that cAMP/Epac achieve intracellular calcium mobilization in human sperm via a pathway involving Rap1 and a PLC.…”
Section: Discussionmentioning
confidence: 99%
“…RyR is a large homotetrameric molecule that contains the calcium release channel of the sarcoplasmic reticulum, and Ca 2+ release is stimulated by ATP, cyclic ADP-ribose and caffeine, and is inhibited by Mg 2+ , H + , ruthenium red and calmodulin [27]. It was revealed that the existence of RY2 in the pancreatic B cells is involved in intracellular Ca 2+ mobilization [18,34], and we have reported that oscillatory [Ca 2+ ] i elevation induced by glucose in Ca 2+ -free medium is blocked by ruthenium red [33]. However, limited information is available for spatial and temporal resolution of repetitive [Ca 2+ ] i elevations evoked by GLP-1 in single cells of pancreatic B cells.…”
Section: Introductionmentioning
confidence: 95%
“…For the Ca 2+ -free experiments, we used a physiological salt solution where Ca 2+ was omitted and 2 mM EGTA was added. Glucose (11 mM) was added to the perfusate for the experiments to measure [Ca 2+ ] i changes [33]. Then, the cells in the dish were transferred to the stage of a confocal laser-scanning microscope (Leica Fluovert, Heidelberg, Germany and Zeiss LSM 510-16, Germany).…”
Section: Ca 2+ Measurement With Clsmmentioning
confidence: 99%